Nutritional status of adolescent girls in Southern Coastal Karnataka, India - Agnes Moira Preethi Dsouza; Nishanth Krishna Kodyalamoole (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: India has a large proportion of the world's adolescents. Adolescents are prone to malnutrition, with rising concerns of the double burden of malnutrition. Girls are found to be more vulnerable to malnutrition and there are several contributing factors. OBJECTIVES: To assess the nutritional status and the factors affecting the nutritional status of adolescent girls. METHODOLOGY: A cross-sectional study was conducted among adolescent girls studying in the 5th to 10th standard in the schools belonging to the field practice area of a Medical College in Southern Coastal Karnataka. The data were collected by the interview method using a questionnaire based on the Global School Health Survey questionnaire for India. The World Health Organization Anthro Plus software was used to calculate the Z-scores. Anemia was evaluated by the clinical examination for pallor. RESULTS: The mean age of the adolescent girls was 12.3 years (standard deviation = 1.7). Early adolescents were more likely to be malnourished (65.7%) and older adolescents were more likely to be stunted (63.9%). The association between the age group and height was found to be significant (χ2 = 49.466, P < 0.001). Body mass index (BMI) was significantly associated with the religion. On clinical examination, 11.4% of the adolescents had clinical pallor. Stunting was more among older adolescents and thinness or low BMI was common among younger adolescents. CONCLUSIONS: Malnutrition was present in around two-thirds of the study population. A dual burden of malnourishment was also observed in this study. Clinical pallor was present more among the malnourished adolescent girls.